A unified droop control of AC microgrids under different line impedances: Revisiting droop control and virtual impedance method - Wang, Lei; Li, Tiecheng; Cheng, Ziwei; Hu, Xuekai; Li, Zifan; Liu, Zhangjie; Huang, Jungao; Hou, Xiaochao (Frontiers in Energy Research, 2023)
Classical droop control and virtual impedance methods play crucial roles in improving the system voltage/frequency stability and autonomous power control. Usually, these two methods are often applied as a combination to facilitate load sharing under different line impedance among distributed generators (DGs) in microgrids. They have been developed in two separate concepts, but present strong similarities. In this paper, the comparison of basic droop control and virtual impedance methods is revisited from a new analogy perspective. By combing both of them, a unified multi-degree-of-freedom droop control is proposed with systematic consideration of steady-state power-sharing performance, dynamic performance, and universal applicability of complex line impedance, which is suitable for arbitrary transmission line impedance characteristics. Moreover, this study gives a clear mechanism analysis of virtual inductance to facilitate the P-f & Q-V droop control in complex resistive-inductive microgrid. Finally, the experiment results verify the feasibility of the proposed unified droop control.